The Improvement in Kyphotic Angle after Anterior Decompression and Cage Placement in Tuberculosis of Thoracolumbar Spine (Medical Forum Monthly, 2023)
Objective: The goal of the research was to ascertain if anterior decompression and cage insertion will reduce the kyphotic Angle in patients with thoracolumbar spine TB. The clinical results of the 200 patients in the trial were assessed to ascertain the effectiveness of this surgical method in treating kyphotic abnormalities caused by spinal TB. Our knowledge of thoracolumbar spine TB surgery and how it affects spinal alignment is improved by the study's results. Study Design: A prospective research Place and Duration of Study: This study was conducted at the Department Orthopaedic Surgery, Khyber Teaching Hospital (KTH), Peshawar from January 2019 and January 2022. Materials and Methods: Study focused on 200 patients with thoracolumbar spine TB. Participants who met the inclusion criteria were recruited in the study. Each patient's demographic data, clinical manifestation, radiological findings, and preoperative kyphotic angles were noted. All patients had anterior decompression and cage installation procedures. Radiographs were taken at regular intervals during the follow-up period to quantify postoperative kyphotic grades, with the final evaluation taking place a year after surgery. In order to determine the degree of correction, the kyphotic Angle was evaluated using recognized radiographic techniques. Results: The study included 200 individuals, with an average age of 37.5 years (123 males and 77 women). Prior to surgery, the average kyphotic Angle was 35.2 degrees. Following anterior decompression and cage installation surgery, the mean postoperative kyphotic Angle was reduced to 15.7 degrees at the 1-year follow-up, indicating a significant improvement in spinal alignment (p 0.001). The kyphotic Angle was corrected on average by 19.5 degrees thanks to the surgical procedure. Conclusion: The findings of this Study show that anterior decompression and cage implantation are successful surgical procedures for treating kyphotic angles in thoracolumbar spine TB patients. The significant improvement in spine alignment demonstrated in this Study emphasizes the need for early surgery to stop severe kyphotic abnormalities and related consequences. These results add to the body of knowledge on the surgical treatment of spinal TB and provide crucial new information for surgeons treating patients with this illness. Additional long-term Study is required to see how long-lasting these surgical results will be.